Single-stranded DNA-binding protein recruits DNA polymerase V to primer termini on RecA-coated DNA - Arad, Gali; Hendel, Ayal; Urbanke, Claus; Curth, Ute; Livneh, Zvi (The Journal of biological chemistry, 2008)
Translesion DNA synthesis (TLS) by DNA polymerase V (polV) in Escherichia coli involves accessory proteins, including RecA and single-stranded DNA-binding protein (SSB). To elucidate the role of SSB in TLS we used an in vitro exonuclease protection assay and found that SSB increases the accessibility of 3' primer termini located at abasic sites in RecA-coated gapped DNA. The mutant SSB-113 protein, which is defective in protein-protein interactions, but not in DNA binding, was as effective as wild-type SSB in increasing primer termini accessibility, but deficient in supporting polV-catalyzed TLS. Consistently, the heterologous SSB proteins gp32, encoded by phage T4, and ICP8, encoded by herpes simplex virus 1, could replace E. coli SSB in the TLS reaction, albeit with lower efficiency. Immunoprecipitation experiments indicated that polV directly interacts with SSB and that this interaction is disrupted by the SSB-113 mutation. Taken together our results suggest that SSB functions to recruit polV to primer termini on RecA-coated DNA, operating by two mechanisms: 1) increasing the accessibility of 3' primer termini caused by binding of SSB to DNA and 2) a direct SSB-polV interaction mediated by the C terminus of SSB.